Penyelesaian Sengketa Pada Perbankan Syariah: Litigasi dan Non-Litigasi - Rahman, Arif; Hasan, Ahmadi; Mariani, Mariani (Sharia Journal and Education Center Publishing, 2026)
The existence of a dual banking system in Indonesia demands legal certainty in the resolution of Islamic economic disputes. This study aims to analyze the dynamics of judicial authority following the Constitutional Court Decision Number 93/PUU-X/2012 and to compare the efficiency of dispute resolution mechanisms through litigation and non-litigation channels. The study finds that the Constitutional Court's decision has ended jurisdictional dualism by affirming the absolute competence of the Religious Courts, which are now supported by the Small Claim Court mechanism to accelerate case resolution to a maximum of 25 working days. On the other hand, non-litigation channels have undergone transformation with the establishment of the Alternative Dispute Resolution Institution for the Financial Services Sector (LAPS SJK), which provides low-cost mediation services for retail consumers, complementing the role of the National Sharia Arbitration Board (BASYARNAS) which focuses on commercial disputes. This research concludes that the choice of dispute resolution forum is no longer based on jurisdictional doubt, but rather on strategic considerations regarding time efficiency, cost, and the need for Sharia scientific specialization.